Determinan Indikasi Transfer Pricing Berdasarkan Pendekatan Transactional Net Margin Method: Bukti Empiris pada Perusahaan Consumer Non-Cyclicals di Indonesia - Paramita, Virya Mukti; Sandra, Amelia (Jurnal Akuntansi, 2026)
Globalization has caused multinational companies to increase in numbers, which led company’s owners competing fiercely to maintain their position in the perspective of economics and business continuity. Many multinational companies use transactions between related parties with different transaction prices between affiliated companies and third parties. The difference of transaction prices is referred to as transfer pricing. Therefore, this study aims to determine the influence of firm size, related party transactions, debt contracts, and tax haven country on indications of transfer pricing. The research objects in this study are non-cyclical consumer companies listed on the Indonesia Stock Exchange for 2020-2022. The research method for this study uses purposive sampling method with a total of 39 samples and for data testing, this study uses multiple linear regression with IBM SPSS version 26. Based on the data processing results, firm size and debt contract has an effect on transfer pricing, meanwhile related party transactions and tax haven country has no effect on transfer pricing.